A Doping Technique that Suppresses Undesirable H2 Evolution Derived from Overall Water Splitting in the Highly Selective Photocatalytic Conversion of CO2 in and by Water. Issue 32 (10th July 2014) - Teramura , Kentaro; Wang, Zheng; Hosokawa , Saburo; Sakata, Yoshihisa; Tanaka , Tsunehiro
Abstract Photocatalytic conversion of CO2 to reduction products, such as CO, HCOOH, HCHO, CH3OH, and CH4, is one of the most attractive propositions for producing green energy by artificial photosynthesis. Herein, we found that Ga2O3 photocatalysts exhibit high conversion of CO2. Doping of Zn species into Ga2O3 suppresses the H2 evolution derived from overall water splitting and, consequently, Zn‐doped, Ag‐modified Ga2O3 exhibits higher selectivity toward CO evolution than bare, Ag‐modified Ga2O3. We observed stoichiometric amounts of evolved O2 together with CO. Mass spectrometry clarified that the carbon source of the evolved CO is not the residual carbon species on the photocatalyst surface, but the CO2 introduced in the gas phase. Doping of the photocatalyst with Zn is expected to ease the adsorption of CO2 on the catalyst surface.